2017
DOI: 10.1097/fpc.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Replication confirms the association of loci in FOXE1, PDE8B, CAPZB and PDE10A with thyroid traits

Abstract: EMRs linked to genomic data in large populations enable validation of genome-wide association studies discoveries without additional genotyping costs. Our replication confirmed at genome-wide significance the association of loci at FOXE1 with hypothyroidism, and PDE8B, CAPZB and PDE10A with serum TSH. A total of 12 SNPs seemed to explain nearly 7% of the serum TSH variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…This approach focuses on associations between genetic variation within pre-specified genes of interest and phenotypes. In this study, a GWAS-identified INSR locus (rs4804416) replicated in a Scottish population was the candidate gene (Soto-Pedre et al, 2017). This gene encodes a preproprotein that is processed to generate two alpha and two beta subunits that work together as a functioning insulin receptor.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This approach focuses on associations between genetic variation within pre-specified genes of interest and phenotypes. In this study, a GWAS-identified INSR locus (rs4804416) replicated in a Scottish population was the candidate gene (Soto-Pedre et al, 2017). This gene encodes a preproprotein that is processed to generate two alpha and two beta subunits that work together as a functioning insulin receptor.…”
Section: Discussionmentioning
confidence: 97%
“…A GWAS-identified INSR locus (rs4804416) associated with average serum TSH concentrations and replicated in the GoDARTS cohort ( Soto-Pedre et al, 2017 ) was the candidate gene. To strengthen the choice of this candidate, additional single-nucleotide polymorphisms (SNPs) associated with TSH were also considered regarding AF in patients on L -thyroxine (see Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Future studies should also investigate potential immunotoxic effects of contaminants and their relationships with diseases in Arctic marine mammals. (Panicker et al, 2010;Soto-Pedre et al, 2017); 2 (Yen, 2001); 3 (Arnaud-Lopez et al, 2008); 4 (Mangelsdorf and Evans, 1995); 5 (Jansen et al, 2005); 6 (van der Spek et al, 2017); 7 (Nicolaides et al, 2010);8 (Cristancho and Lazar, 2011;Desvergne et al, 2006;Makowski et al, 2005;Ohashi et al, 2010); 9 (Capone et al, 2016;Maltais et al, 2006;Matesanz-Isabel et al, 2011;Polson et al, 2006); 10 (Teft et al, 2006;Waterhouse et al, 1996); 11 (Malek and Castro, 2010); 12 (Jofra et al, 2017); 13 (Elgueta et al, 2009); 14 (Ciofani and Zuniga-Pflucker, 2005;Radtke et al, 1999); 15 (Malathi et al, 2007) PeCB,oxychlordane,transnonachlor,Mirex,p,BDE47 and BDE153 b PFHxS, PFOS, PFOA, PFNA and PFDA Table 3. Transcript levels of genes of interest determined in a) blubber and b) blood cells explained by blubber concentrations of persistent organic pollutants (POP) and plasma concentrations of perfluoroalkyl substances (PFAS) in adult male walruses.…”
Section: Discussionmentioning
confidence: 99%